Comparison of hybrid 68Ga-PSMA PET/MRI and 68Ga-PSMA PET/CT in the evaluation of lymph node and bone metastases of prostate cancer - Freitag, Martin T.; Radtke, Jan Philipp; Hadaschik, Boris; Kopp-Schneider, Annette; Eder, Matthias; Kopka, Klaus; Haberkorn, Uwe; Röthke, Matthias C.; Schlemmer, Heinz-Peter; Afshar-Oromieh, Ali (European journal of nuclear medicine and molecular imaging, 2016)
To evaluate the reproducibility of the combination of hybrid PET/MRI and the 68Ga-PSMA-11 tracer in depicting lymph node (LN) and bone metastases of prostate cancer (PC) in comparison with that of PET/CT.
Im Titel ist „68“ hochgestellt
Published online: 28 October 2015
Gesehen am 26.05.2020